Internet access in libraries : a comparison of press coverage between Canada and Singapore - Luyt, Brendan (2012)
This article compares the newspaper coverage of Internet access in public libraries across two countries, Canada and Singapore. The aim is to discover some of the main concerns and themes that the press identifies with libraries, noting the differences between the two countries in this regard, and then to provisionally link these differences to certain structural characteristics of their respective societies and states. To achieve these aims I compare press coverage produced in terms of dates of publication, discourse producers, and discourse content. Implications of the findings for libraries and librarians are discussed.